EFFECT OF STAKEHOLDERS SUPPORT ON PERFORMANCE OF ORPHAN AND VULNERABLE CHILDREN HOMES IN NAKURU COUNTY - CHEPTOO, CYNTHIA (My University, 2024)
The number of orphans and vulnerable children in the developing world have reached crisis proportions. The number of orphaned children in Sub-Saharan Africa has increased, putting a strain on the ability of many countries to care for them. The main aim of this study was to determine the effect of stakeholder’s support on performance of orphan and vulnerable children homes in Nakuru County. The specific objectives of the study were; to establish the effect of donor support on performance of orphan and vulnerable children homes in Nakuru County, Kenya, to evaluate the effect of community support in performance of orphan and vulnerable children homes in Nakuru County, Kenya, to ascertain the effect of County government support on implementation orphan and vulnerable children homes in Nakuru County, Kenya and to determine the effect of Employee Support on performance of orphan and vulnerable children homes in Nakuru County, Kenya. The study adopted the social exchange theory and stakeholder theories. The target population of the study was 188 respondents responsible for daily activities in the children homes from the 38 registered and operational children homes in the county. The sample size was128 respondents obtained using Tora Yamane’s formula. The data was collected through the administration of structured closed-ended questionnaires. Content validity in the study questionnaires was achieved through expert judgment of the research supervisors. The Cronbach’s Alpha test was used to test the reliability of the instruments with a threshold of greater than 0.7Descriptive and inferential statistics was used to analyze data. The results of the study were presented in tables, figures and frequency tables. The study revealed that the support provided by the county government is enough to enable the children home run without facing challenges. The study also revealed that the financial support from the county government has enabled the homes to provide quality care to the children. The study found that there was a moderate positive and statistically significant correlation between donor support and performance of orphan and vulnerable Children homes in Nakuru County, Kenya, (r = 0.632; p=0.015). The study also found that there was a moderate positive correlation existed between community support on performance of orphan and vulnerable Children homes in Nakuru County, Kenya, (r = 0.464; p=0.000). Moreover, the study found that there was a moderate positive correlation existed between county government support and performance of orphan and vulnerable Children homes in Nakuru County, Kenya(r = 0.469; p=0.000). The study concluded that donor, community, county government and employee support all have a moderate positive and statistically significant impact on the performance of orphan and vulnerable children homes in Nakuru County Kenya. Based on these findings, it is recommended that existing policies be reinforced through better implementation and oversight to enhance donor, community, county government and employee support for orphan, ensuring county government allocate sufficient resources following best practices and improve employee welfare through standardized training and career development programs. This study proposes further research to explore the long-term impact of donor and community support on child outcomes, to evaluate the effectiveness of county-level government policies and to assess the role of public-private partnerships in enhancing service delivery.
Keywords: Donor Support, Community Support, County Government Support, Employee Support, Orphan and Vulnerable Children